Digital Intelligence Empowerment and Group Differentiation: Information Behavior and Intervention Pathways in Health Communication: A Review Based on Panel 4 of MHM 2025 (The Journal of Medicine, Humanity and Media, 2025)
On July 6, 2025, the 8th “Medicine, Humanity and Media” Health Communication International Conference & Doctoral Symposium was held at Peking University. This panel report summarizes six research presentations delivered during Panel 4 of the MHM2025 International Conference, themed “Digital Intelligence Empowerment and Group Differentiation: Information Behavior and Intervention Pathways in Health Communication.” The research topics address fact-check label efficacy on short-video platforms, discourse evolution of monkeypox narratives, technological emotion and youth resilience, internet use as a mediator of elderly depression, older adults’ health information seeking, and health information engagement among pregnant women. The panel highlights how digital empowerment intersects with social differentiation, offering nuanced insights into health misinformation correction, digital literacy, and culturally situated intervention design.
Keywords: Health communication; Information behavior; Digital literacy; Misinformation correction; Vulnerable populations